Gene Expression Differences in Prostate Cancers between Young and Old Men. - Yuanchun Ding; Huiqing Wu; Charles Warden; Linda Steele; Xueli Liu; M van Iterson; Xiwei Wu; Rebecca Nelson; Zheng Liu; Yate-Ching Yuan; Susan L Neuhausen (PLoS Genetics, 2016)
Prostate cancer incidence is increasing in younger men. We investigated whether men diagnosed with Gleason 7 (3+4) T2 prostate cancer at younger ages (≤ 45 years, young cohort) had different mRNA and miRNA expression profiles than men diagnosed at older ages (71-74 years, older cohort). We identified differentially expressed genes (DEGs) related to tumor-normal differences between the cohorts. Subsequent pathway analysis of DEGs revealed that the young cohort had significantly more pronounced inflammatory and immune responses to tumor development compared to the older cohort. Further supporting a role of inflammation-induced immune-suppression in the development of early-onset prostate cancer, we observed significant up-regulation of CTLA4 and IDO1/TDO2 pathways in tumors of the young cohort. Moreover, over-expression of CTLA4 and IDO1 was significantly associated with biochemical recurrence. Our results provide clues on the mechanisms of tumor development and point to potential biomarkers for early detection and treatment for prostate cancer in young men.